Species Diversity and Assemblage of Mangroves at Setiu Wetland, Terengganu, Malaysia: Species diversity and assemblage of mangroves, Malaysia - RAHMAN, ABUL FAIZ MOHAMMAD ARIFUR; ISLAM, MOHAMMAD AHSANUL; IDRIS, MOHD HANAFI; BHUIYAN, MD KHURSHID ALAM; CHOWDHURY, MOHAMMAD MAMUN; ABUALREESH, MUYASSAR H.; ABU HENA MUSTAFA KAMAL (Borneo Journal of Resource Science and Technology, 2023)
Mangroves in wetland ecosystems are diverse and play significant role in the adjacent communities on which they are dependent for their livelihoods. It is also important for fishery resources and nutrient inputs in marine and brackish water ecosystems. However, little is known about the tropical wetland lagoon ecosystems, particularly mangrove diversity and assemblages. Therefore, this present study was initiated to observe the mangrove species diversity and assemblages together with the conservation status in an important tropical wetland ecosystem in Setiu, Terengganu, Malaysia. In a variety of landward and small fringe island areas, three zones of square plots were selected (zones 1, 2 and 3) to address the objectives of this study. As a result, a total of 20 true mangrove species belonging to 11 genera from nine families were documented, of which, Avicennia rumphiana was listed as vulnerable (VU) by the IUCN. Twelve species of mangrove associates from 11 genera and nine families were also found in the investigated zones at Setiu. One of the mangrove associates, Intsia bijuga, was designated as vulnerable (VU) by the IUCN. The Shannon diversity index (H’) of mangroves was found to be 1.08 at Setiu Wetland. Rhizophora mucronata was found to be well-expanded (H’ = 1.05) followed by A. rumphiana, A. officinalis, Heritiera littoralis, A. corniculatum. Excoecaria agallocha, Lumnitzera racemosa, and A. ebracteatus (H’ = 0.0) as the lowest. The findings of the present study revealed that mangroves in the Setiu Wetland are diverse and healthy compared to other mangrove ecosystems in the region. To maintain the health and function of the mangrove ecosystem in Setiu Wetland, proper monitoring is required.